Circular economy practices as a shield for the long-term organisational and network resilience during crisis: Insights from an industrial symbiosis - Karman, Agnieszka; Prokop, Viktor; Jabbour, Ana Beatriz Lopes Sousa (Elsevier Science, 2024)
This study examines the impact of circular economy (CE) practices in achieving long-term organisational and network resilience after Covid-19 in the case of an industrial symbiosis within the hitherto less explored area of Central and Eastern Europe. Our original findings based on primary data demonstrate that CE practices trigger organisational resilience through resilience capabilities, flexibility, and cooperation and that organisational resilience can be positively reflected in network resilience and robustness. Moreover, organisational resilience positively influences network resilience and robustness within industrial symbiosis. The results confirm the hypothesis that companies with a higher level of CE practices demonstrate greater resilience over the long term compared to their peers. This research offers several contributions, ranging from an original theoretical framework based on the (natural) resource-based view, dynamic capabilities, and organisational resilience to practical contributions to developing organisational adaptive capacity in networks of industrial symbiosis in crisis.
Praktiky oběhové ekonomiky jako štít pro dlouhodobou odolnost organizace a sítě během krize: Postřehy z průmyslové symbiózy
Keywords: Circular economy; Industrial symbiosis; Resilience; Central and Eastern Europe; oběhové hospodářství; Průmyslová symbióza; odolnost; střední a východní Evropy